Solution-Driven Software Product Line Engineering - Groher, Iris; Fiege, Ludger; Elsner, Christoph; Schwanninger, Christa; Völter, Markus (Aspect-Oriented, Model-Driven Software Product Lines - The AMPLE Way, 2011)
As described in Chapters 1, 2 and 10, the product- and solution-driven businesses found in industrial settings have different needs on tools and methods. They do not require completely disparate approaches, but their respective focus emphasises different parts of the product line engineering process and its tools. A one-size-fits-all approach to PLE is not feasible.This chapter investigates the characteristics of solution-driven business from the PLE perspective and shows how PLE tools and techniques presented in the previous chapters can be applied in such a setting.
UnivIS-Import:2015-04-20:Pub.2011.tech.IMMD.IMMD4.soluti